Sex-related differential item functioning of neck disability index - Saltychev Mikhail; Widbom-Kolhanen Sara S; Pernaa Katri I (Taylor & Francis Ltd, 2025)
Purpose: To investigate if the responses to the Neck Disability Index (NDI) may produce some differential item functioning (DIF) comparing men and women.
Materials and methods: Register-based study among patients undergoing cervical surgery. Item response theory (IRT) analysis including a model for detecting a DIF.
Results: Of 338 patients, 171 (51%) were women and 167 (49%) were men. The mean age was 54.0 years. For most of the items, the average level of disability in a studied sample was associated with the middle point of the scale. The ability to distinguish people with different levels of disability was high or perfect for seven out of 10 items. While the DIF could be seen for all 10 items, only three items demonstrated statistically significant DIF - "pain intensity", "headaches" and "recreation". While the other seven items did not show statistically significant DIFs, better discrimination (steeper curves) for women could be graphically observed for "personal care", "lifting", "work", "driving" and "sleeping".
Conclusions: It seemed that the NDI may behave differently depending on the sex of respondents. Several items of the NDI may be more precise and more sensitive when detecting restrictions in functioning among women compared to men. This finding should be taken into account when using the NDI in research and clinical practice.Implications for RehabilitationWhile the Neck Disability Index have been found to be a reliable and valid scale, potential differences in its properties across different sexes have mostly remained uninvestigated.This study showed that the Neck Disability Index may behave differently depending on the sex of respondents.Several items of the Neck Disability Index were more precise and sensitive when detecting restrictions in functioning among women compared to men.This difference should be taken into account when using the NDI in research and clinical practice.